2021
DOI: 10.3390/app11073011
|View full text |Cite
|
Sign up to set email alerts
|

Human Laryngeal Mucus from the Vocal Folds: Rheological Characterization by Particle Tracking Microrheology and Oscillatory Shear Rheology

Abstract: Mucus consistency affects voice physiology and is connected to voice disorders. Nevertheless, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Small volume rheology is also required for pathological analysis of the vitreous, a fluid that fills the eye [63][64][65][66][67] as well as severity analysis of lung infection 68 and vocal disorders. 69 The total vitreous volume in human eyes is about 4 ml, 70 while the collected volume of human laryngeal mucus ranges from 10 μl to 1.8ml. 69 The ATS enables safe and reliable analysis of these fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small volume rheology is also required for pathological analysis of the vitreous, a fluid that fills the eye [63][64][65][66][67] as well as severity analysis of lung infection 68 and vocal disorders. 69 The total vitreous volume in human eyes is about 4 ml, 70 while the collected volume of human laryngeal mucus ranges from 10 μl to 1.8ml. 69 The ATS enables safe and reliable analysis of these fluids.…”
Section: Discussionmentioning
confidence: 99%
“…69 The total vitreous volume in human eyes is about 4 ml, 70 while the collected volume of human laryngeal mucus ranges from 10 μl to 1.8ml. 69 The ATS enables safe and reliable analysis of these fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rheological properties of lung and airway mucus have been tied to disease states for many respiratory ailments: cystic fibrosis, laryngeal tuberculosis, bronchitis, asthma, chronic obstructive pulmonary disorder (COPD), voice disorders, and lung plaque buildup from smoking ( Lai et al, 2009b ; Lin et al, 2020 ; Peters et al, 2021 ). The microrheology of pulmonary mucus also directly affects the movement of this protective barrier throughout the lung and airway and, therefore, its effectiveness as a protective barrier.…”
Section: Microrheological Approaches To Evaluate Mechanical Propertie...mentioning
confidence: 99%
“…Respiratory mucus originating from the vocal cords plays an essential role in voice disorder pathology in smokers. Recently, researchers investigated laryngeal mucus collected from the vocal folds of smokers and non-smokers using both VPT and bulk rheology ( Peters et al, 2021 ). Both methods uncovered gel-like characteristics in all groups; however, mucus rigidity varied depending on the smoking habits of the subject.…”
Section: Microrheological Approaches To Evaluate Mechanical Propertie...mentioning
confidence: 99%
“…The influence of laryngeal mucus towards vocal fold oscillations has been discussed during the last few years. Peters et al [14] perform rheological characterization by particle tracking micro-rheology and oscillatory shear rheology on human mucus to gain further insight into viscoelasticity. In their preliminary study, they found great diversity and grouped the mucus samples in three categories.…”
Section: Machine Learningmentioning
confidence: 99%